Association between socioenvironmental Factors and the practice Of physical activity in pregnant women: A cross-sectional study (2018)
Objective: To establish the relationship between social and environmental determinants and the practice of physical activity in pregnant women. Materials and methods: Cross-section study conducted in pregnant women with no contraindication to physical activity; these women came for prenatal consultation and were affiliated to two healthcare providers in Barranquilla and Cartagena de Indias, Colombia. Sampling was intentional. The social and demographic characteristics were evaluated, as well as the levels of physical activity and the perception of socio-environmental factors, including neighborhood infrastructure, esthetic considerations, the social environment, road connectivity, safety and surrounding traffic conditions. The raw Odds Ratio (OR) was estimated. Results: Out of 228 pregnant women, 208 were included in the analysis. 62% of the pregnant women fail to comply with the physical activity recommendations for maintaining their health. Some of the socio-environmental factors associated with a sedentary lifestyle in pregnancy are: living far away to walk to shops and supermarkets (OR = 5.1; 95 % CI: 2.8-9.4); poor sidewalk conditions (OR = 3.4; 95 % CI: 1.9-6.3); few people exercising around the neighborhood (OR = 4.1; 95 % CI: 2.2-7.5); not safe to walk during the day or evening (OR = 3.6; 95 % CI: 1.9-6.4). Conclusion: The perception of the socio-environmental characteristics is associated with physical activity in pregnant women. Interventions are needed to improve the socio-environmental characteristics that impact the perception of the population about these factors, in order to assess its impact on the physical activity of pregnant women.